TINJAUAN LITERATUR GENDER DIVERSITY TERHADAP SUKSES BISNIS RINTISAN - Santoso, Rudi (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2025)
Research aim: This research seeks to explain the role of gender in the success of start-up businesses in Indonesia, especially in Surabaya. Method: This descriptive qualitative study uses a literature review approach. Research Finding: Research has found that gender differences can determine the color and type of business people choose. Theoretical Contribution: The difference in treatment in terms of gender has implications for different results for start-up businesses. Practical implications: This research contributes to the business and industrial world by examining how to manage women's psychology to improve business. It also found that most business owners are women. Research limitation: The locus of study is limited to the city of Surabaya.